Mechanical responses and fracturing behaviors of coal under complex normal and shear stresses, Part II: Numerical study using DEM - Z. Y. Song; F. Amann; W. G. Dang; Z. Yang (International Journal of Coal Science & Technology, 2024)
Abstract This work presents particle-based numerical simulations on coal pillars in a coal mine based underground water reservoir (CMUWR). We aim to replicate the stress–strain characteristics and present the acoustic emission behavior of the coal under complex dynamic stress paths. The study reveals failure characteristics of coal exposed to monotonic/cyclic shear load under constant/cyclic normal loads. Based on the evolution of stress-time-dependent bond diameter implemented in particle model, different damage paths are established for dry and water-immersed samples under two loading frequencies. Furthermore, the numerical Gutenberg–Richter’s b-value was calculated from the released energy emanating from bond failure, and this work presents the evolution of numerical Gutenberg–Richter’s b-value. The numerical simulation contributes to a micromechanical understanding of the failure mechanisms of coal under water-immersion and cyclic stress, providing valuable insights for strength prediction of CMUWR.